2017
DOI: 10.1177/0972150916666879
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Childcare Teacher Retention in the Childcare Service Industry

Abstract: There is relatively little research on teacher retention in the Singaporean early childhood industry, yet this is an important workforce issue because of the rapid expansion of childcare centres to meet the growing needs of parents in Singapore. This qualitative study aims to identify the dominant, contemporary factors that influence childcare teachers’ intentions to continue working in the Singaporean childcare industry. The unit of analysis is the individual; hence, the focus of investigation is on the lived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Meanwhile, in a study of 316 nurses based in Ibero-American countries, it was revealed that both burnout and work engagement affect turnover intention. [29] Other studies have shown that job demand and job control affect work engagement, [30] and that poor workplace environments may lower work engagement [7] and may increase turnover intention. Meanwhile, conversely, a good working environment has been shown to lower turnover intention.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Meanwhile, in a study of 316 nurses based in Ibero-American countries, it was revealed that both burnout and work engagement affect turnover intention. [29] Other studies have shown that job demand and job control affect work engagement, [30] and that poor workplace environments may lower work engagement [7] and may increase turnover intention. Meanwhile, conversely, a good working environment has been shown to lower turnover intention.…”
Section: Discussionmentioning
confidence: 99%
“…However, permanent employment was not important for the under-39 seconds. Good rewards and welfare are known to contribute to the suppression of turnover intention; [1,7,13] thus, for individuals over the age of 40, there is a possibility that good treatment in regard to employment may lead to lower job-separation desire.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations